Progressive facial hemiatrophy - A case series - Feroze Kaliyadan; Kaberi Biswas; A D Dharmaratnam (Wolters Kluwer Medknow Publications, 2011)
Six female patients diagnosed with Progressive Facial Hemiatrophy are presented here. The clinical and serological features are highlighted, and treatment options for the condition are discussed. We would like to highlight the need to differentiate the condition from localized scleroderma and the with limitation of its medical management.